Relationships between woody vegetation and geomorphological patterns in three gravel-bed rivers with different intensities of anthropogenic disturbance. (July 2016) - Sitzia, T.; Picco, L.; Ravazzolo, D.; Comiti, F.; Mao, L.; Lenzi, M.A.
Highlights: We compare three gravel-bed rivers which vary in anthropogenic disturbance. Human-related degradation is discriminated by morphological and stand variability. Woody species distribution interacts with mean grain size and geomorphic persistence. Intermediate-disturbed river has unusual high heterogeneity of woody species amplitude. Abstract: We compared three gravel-bed rivers in north-eastern Italy (Brenta, Piave, Tagliamento) having similar bioclimate, geology and fluvial morphology, but affected by different intensities of anthropogenic disturbance related particularly to hydropower dams, training works and instream gravel mining. Our aim was to test whether a corresponding difference in the interactions between vegetation and geomorphological patterns existed among the three rivers. In equally spaced and sized plots ( n = 710) we collected descriptors of geomorphic conditions, and presence–absence of woody species. In the less disturbed river (Tagliamento), spatial succession of woody communities from the floodplain to the channel followed a profile where higher elevation floodplains featured more developed tree communities, and lower elevation islands and bars were covered by pioneer communities. In the intermediate-disturbed river (Piave), islands and floodplains lay at similar elevation and both showed species indicators of mature developed communities. In the most disturbed river (Brenta), all these patterns were simplified, all geomorphic units lay at similar elevations, were not well characterized by species composition, and presented similar persistence age. This indicates that in human-disturbed rivers, channel and vegetation adjustments are closely linked in the long term, and suggests that intermediate levels of anthropogenic disturbance, such as those encountered in the Piave River, could counteract the natural, more dynamic conditions that may periodically fragment vegetated landscapes in natural rivers.